PENGEMBANGAN APLIKASI "PILIH JURUSAN" BERBASISWEBSITE DENGAN METODE SCRUM PADAPT. PILIHANMU INDONESIA JAYA - Rafika Rona Fairuz (2022)
PT. Pilihanmu Indonesia Jaya has a website called Pilih Jurusan. Pilih Jurusan is an alternative space for students to discover their potential through online career guidance. However, the Pilih Jurusan website still has some shortcomings in terms of functionality, usability, and performance, therefore it is necessary to develop a Pilih Jurusan website to create excellent service for all Pilih Jurusan services. This study aims to build a website for junior high school or senior high school students to be able to do psychological tests to find out their interests and talents and make it easier for admins to manage test result data. The research methodology used in this study is the scrum methodology which is very useful in time efficiency of the software development process, then designed using UML (Unified Modeling Language) and built using the codeigniter framework with mariadb as the database server. The results obtained from this study are a website-based application which is an online psychological test application that can be used by students of junior high school or senior high school and Vice President Operations of PT. Your choice Indonesia Jaya. With this application, it can minimize existing problems such as test instructions that are difficult to achieve and lack of time efficiency in the test procedure.